A Small Low-Cost SAR Satellite for InSAR Measurements of Permanent Scatterers - Hounam, David; Moreira, Alberto; Mittermayer, Josef; Krieger, Gerhard (European Conference on Synthetic Aperture Radar (EUSAR), 2004)
A major driver for the cost of a SAR satellite is the size of the antenna, which largely determines the dimensions of the payload, and, hence, indirectly of the whole satellite. Apart from influencing the sensitivity of the SAR, the dimensions of the SAR antenna also determine the width of the imaged swath and the strength of ambiguous responses. Ambiguities appear as ghosts or additional noise in the image. Techniques are discussed for suppress-ing ambiguities during processing, which are demonstrated to be viable for point targets. Targets with scattering characteristics which are stable over long periods of time can be used with interferometric SAR (InSAR) techniques to monitor small displacements. As these so-called permanent scatterers have point target characteristics and a relatively high RCS, a SAR instrument with a small antenna can be considered. It has been demonstrated that an interferometric SAR system measuring the long-term motion of permanent scatterers placed in geologically instable regions can serve a range of important and lucrative applications.
DLR Import::2019-04-03